2019
DOI: 10.1161/circinterventions.118.007232
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cost of Care by Palliation Strategy for Infants With Ductal-Dependent Pulmonary Blood Flow

Abstract: Background:In infants with ductal-dependent pulmonary blood flow (PBF), initial palliation with patent ductus arteriosus (PDA) stent or modified Blalock-Taussig (BT) shunt have comparable mortality but discrepant length of stay (LOS), procedural complication rates and reintervention burdens, which may influence cost. The relative economic impact of these palliation strategies is unknown. Methods and Results:Retrospective study of infants with ductal-dependent PBF palliated with PDA stent (n=104) or BT shunt (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
(42 reference statements)
0
28
0
Order By: Relevance
“…According to the inclusion and exclusion criteria, six studies (from 2009 to 2018, involving 757 patients) were included in the analysis [ 16 21 ]. Three studies used the same database, and we included only the largest one by Glatz et al for the synthetic analysis [ 20 , 22 , 23 ]. The detailed literature screen steps are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the inclusion and exclusion criteria, six studies (from 2009 to 2018, involving 757 patients) were included in the analysis [ 16 21 ]. Three studies used the same database, and we included only the largest one by Glatz et al for the synthetic analysis [ 20 , 22 , 23 ]. The detailed literature screen steps are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Relatively, the length of ICU stay and hospital stay were both shorter according to the studies by Glatz et al and Bentham et al [ 20 , 21 ]. Furthermore, Goldtein et al compared the costs for hospitalization and the first year of life between the two groups and found that there were lower costs for patients who received stent implantation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDA stenting remains an important means of palliating infants with cyanotic congenital heart disease with the potential to reduce morbidity and costs of care in this population . To date, there have not been any reports of bronchial compression after PDA stent angioplasty.…”
Section: Resultsmentioning
confidence: 99%
“…Glatz et al 6 reported similar mortality and freedom from unplanned interventions between both methods; however, balanced pulmonary artery growth favored PDA stenting. On the other hand, Goldstein et al 3 reported comparable pulmonary artery growth with no difference in pulmonary artery reconstruction required at the second stage for both groups. Moreover, the cost of care after PDA stenting during the first year of life was lower than equivalent MBTS patients.…”
Section: Introductionmentioning
confidence: 97%
“…2 With the advantage of avoiding potential surgical complications, the use of PDA stenting continues to grow. 3 However, PDA stenting has issues related to vascular access and stent-related complications. 4,5 Few studies have compared the clinical outcomes of PDA stenting and MBTS as first-stage palliation of duct-dependent PBF lesions.…”
Section: Introductionmentioning
confidence: 99%